A Case Report of Posterior Reversible Encephalopathy Syndrome (PRES) in a Nonsevere Case of COVID-19 - Małgorzata Cisowska-Adamiak; Katarzyna Sakwińska; Iwona Szymkuć-Bukowska; Anna Goclik; Iwona Lunitz; Magdalena Mackiewicz-Milewska (Brain Sciences, 2022)
Posterior reversible encephalopathy syndrome (PRES) is a rare complication that the exact pathophysiological mechanism of which is still unclear. PRES most often occurs in connection with severe hypertension and autoimmune diseases. It can also appear during chemotherapy or immunosuppressive treatment. A 38-year-old woman with a negative medical history was admitted to the local hospital due to loss of consciousness accompanied by seizures and high values of blood pressure, and a PCR test for COVID-19 was positive. The patient’s condition was preceded by weakness, wet cough, runny nose, and low-grade fever for three days. Due to the conducted diagnostics after negative CT scans and angio CT studies, an MRI of the head with contrast was performed, where changes characteristic of PRES syndrome were found. During the hospitalization, the patient did not require invasive ventilation and did not receive antiviral drugs or tocilizumab as a result of treatment for her high blood pressure values, and after establishing the diagnosis, the patient was discharged home with a significant improvement in her well-being. In the literature, there are discussions as to whether COVID-19 predisposes patients to PRES. Isolated cases have been described, but its frequency is not yet established. Case reports in the literature appear to be specifically associated with a severe course of the disease, unlike in our patient. Even with a mild course of COVID, the diagnosis of PRES should be taken into account in patients with seizures, visual disturbances, or other focal neurological deficits.